2018
DOI: 10.1186/s40479-018-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation in attention-deficit/hyperactivity disorder and borderline personality disorder

Abstract: There is ongoing debate on the overlap between Attention-Deficit/Hyperactivity Disorder (ADHD) and Borderline Personality Disorder (BPD), particularly regarding emotion dysregulation (ED). In this paper, we present a narrative review of the available evidence on the association of these two disorders from several standpoints. First, we discuss the unique and shared diagnostic criteria for ADHD and BPD, focusing particularly on ED. We consider the methodology of ecological momentary assessment and discuss why t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 116 publications
0
42
1
2
Order By: Relevance
“…Thus, our results are not representative of the non-severe cases of ADHD. It is well known that both ADHD and BPD are highly associated with other psychiatric disorders and behavioral problems [36,37]. However, our study revealed that the ADHD+BPD group demonstrated a greater number of psychiatric symptoms and behavioral problems compared to the ADHD or BPD groups.…”
Section: Discussioncontrasting
confidence: 65%
“…Thus, our results are not representative of the non-severe cases of ADHD. It is well known that both ADHD and BPD are highly associated with other psychiatric disorders and behavioral problems [36,37]. However, our study revealed that the ADHD+BPD group demonstrated a greater number of psychiatric symptoms and behavioral problems compared to the ADHD or BPD groups.…”
Section: Discussioncontrasting
confidence: 65%
“…Both ADHD and borderline personality disorder (BPD) may be considered developmental since they emerge during childhood or adolescence [182]. ADHD and BPD share similar clinical features including impulsivity, affective instability, emotional dysregulation, and unstable interpersonal relationships [182][183][184].…”
Section: Differential Diagnosis and Comorbiditymentioning
confidence: 99%
“…Both ADHD and borderline personality disorder (BPD) may be considered developmental since they emerge during childhood or adolescence [182]. ADHD and BPD share similar clinical features including impulsivity, affective instability, emotional dysregulation, and unstable interpersonal relationships [182][183][184]. On the other hand, symptoms such as chronic suicidality, self-mutilation, feelings of abandonment and emptiness, stress-related paranoid ideation or dissociation are typical of BPD but not of ADHD [184,185].…”
Section: Differential Diagnosis and Comorbiditymentioning
confidence: 99%
“…Emotional dysregulation (ED) is a set of symptoms that have been considered a core clinical feature of BPD and have been assigned a key role in the main etiopathogenic models of the disorder [5]. However, in recent years, the number of studies highlighting the relevant role that ED can also play in ADHD [6,7] has increased. For differential diagnosis, suicidal behavior has been considered more typical of BPD than of ADHD [8], whereas primary attentional cognitive deficits are significantly more frequent in ADHD than in BPD [8,9].…”
Section: Introductionmentioning
confidence: 99%